Chronopharmacology of intrathecal sufentanil for labor analgesia: daily variations in duration of action - Debon, Richard; Boselli, Emmanuel; Guyot, Romain; Allaouchiche, Bernard; Lemmer, Björn; Chassard, Dominique (Anesthesiology, 2004)
The pharmacokinetic and pharmacodynamic characteristics of opioids vary throughout the day, as demonstrated for oral morphine in chronic pain. However, little is known about the chronobiology of intrathecal lipid soluble opioids used for labor analgesia. The aim of this prospective study was to determine whether the duration of action of intrathecally administered sufentanil is influenced by the time of administration.Ninety-one women in the first stage of labor were enrolled. Labor analgesia was first provided by 10 microg intrathecal sufentanil. The duration of action of intrathecal sufentanil was measured and analyzed by the cosinor method to determine periodic intraday variation.Pain assessed by a visual analog score was not different among patients (70 +/- 17 mm) before the injection of intrathecal sufentanil. Rhythm analysis revealed a mean ( +/- SD) duration of analgesia (mesor) of 93.0 +/- 3.8 min. A highly significant 12-h rhythm was found, with two peaks: One was near midnight (0.78 +/- 0.6 h), and the other was near noon (12.78 +/- 0.6 min) (P < 0.01). The amplitude of this 12-h component was 16.1 +/- 5.5 min.The duration of intrathecal sufentanil analgesia exhibited a temporal pattern with 30% variations throughout the day period. The authors point out that the lack of consideration of chronobiological conditions in intrathecally administered analgesia studies can cause significant statistical bias. Further studies dealing with intrathecal opioids should consider the time of drug administration.